Detection of pathogens from periodontal lesions - Malheiros Veruska de João; Avila-Campos Mario Julio (Universidade de São Paulo, 2004)
OBJECTIVE: To comparatively detect A. actinomycetemcomitans and F. nucleatum from periodontal and healthy sites. METHODS: Subgingival clinical samples from 50 periodontitis adult patients and 50 healthy subjects were analyzed. Both organisms were isolated using a trypticase soy agar-bacitracin-vancomycin (TSBV) medium and detected by PCR. Conventional biochemical tests were used for bacteria identification. RESULTS: A. actinomycetemcomitans and F. nucleatum were isolated in 18% and 20% of the patients, respectively, and in 2% and 24% of healthy subjects. Among A. actinomycetemcomitans isolates, biotype II was the most prevalent. Primer pair AA was 100% sensitive in the detection of A. actinomycetemcomitans from both subject groups. Primers ASH and FU were also 100% sensitive to detect this organism in healthy subject samples. Primer pair FN5047 was more sensitive to detect F. nucleatum in patients or in healthy samples than primer 5059S. Primers ASH and 5059S were more specific in the detection of A. actinomycetemcomitans and F. nucleatum, respectively, in patients and in healthy subject samples. CONCLUSIONS: PCR is an effective tool for detecting periodontal pathogens in subgingival samples, providing a faster and safer diagnostic tool of periodontal diseases. The method's sensitivity and specificity is conditioned by the choice of the set of primers used.